THE EFFECT OF DER, TATO, ROA AND SHARE PRICE TO PBV (Studies on the food and beverage industry on the Indonesia Stock Exchange period of 2012-2018) - Firdaus, Iwan (Dinasti Publisher, 2020)
This research is to find out the influence of DER, TATO, ROA and Share Price to PBV on companies listed in Indonesia Stock Exchange retail sub sector ffod and beverage period 2012-2019. The sample selection in this research using saturated sampling method and got 7 companies that match the criteria, so that 49 data were obtained. The research data is obtained from Indonesia Stock Exchange. The method used in this research is panel data multiple regression analysis and it is found that the more appropriate model used is fixed effect. From result of research got value of adjusted R-Square equal to 79,12%. Partially show that DER have negative and significant effect to PBV. TATO, Share Price variable partially had positive and significant effect to PBV. ROA variable partially have positive and no significant effect to PBV.